Analysis of The Causes of Negligence of Homework in Elementary School Students in Iraq - Alshatri, Shwan Hussein (Universitas Islam Negeri Raden Intan Lampung, 2023)
In this research, one of the main problems that students face in school is neglecting assignments and homework. This information was found to be a fundamental cause affecting the whole learning process, such as in science lessons. This research aims to raise awareness of task neglect among teachers, students, and their families and raise the level of students by teaching them how to prioritize homework. The study was conducted in several elementary schools in the province of Sulaymaniyah in the Iraqi Kurdistan Region, using a descriptive method on cadastral forms related to homework neglect. There are 10, 5, and 9 questions related to teachers, families, and students. The study results show that teachers and families are the most influential factors in student performance in completing homework. It is suggested that in the future, for further research on the same subject, a technique can be applied to reduce the level of neglect of homework in students.